Krough House - Kjysten Drew:::Creator::::::::::::
Krough House. 148 Central Avenue, Salinas, California. Olga Krough was a playmate of John Steinbeck's. Krough's drugstore makes an appearance in East of Eden (p.711). Original is slide.